“My Own Worst Enemy”: Translating Hamartia in Sixteenth-Century Italy. - BRAZEAU, BRYAN (Renaissance & Reformation / Renaissance et Réforme, 2018)
This article considers the ways in which Aristotle's notion of hamartia (άμάαρτíα) in the Poetics—the tragic fault that leads to the protagonist's downfall—was rendered in sixteenth-century translations and commentaries produced in Italy. While early Latin translations and commentaries initially translated the term as error, mid-Cinquecento literary critics and theorists frequently used a term that implied sin: peccatum/peccato. Was this linguistic choice among sixteenth-century translators indicative of a broader attempt to Christianize the Poetics? While there were significant attempts on the part of translators and commentators to moralize the Poetics, this study of how hamartia was translated suggests that such interpretations were not Counter-Reformation distortions o f Aristotle’s Poetics but rather part of a broader program of cultural translation—expressing the linguistic influence of a religious public, but not necessarily a moralizing interpretation—domesticating the Greek philosopher for an early modern Christian audience.